High School Student\'s Knowledge About the Effects of Ecstasy Druge in District Nine of Tehran City - Alireza Kaldi; Mehdi Rahgozar; Mehrdad Navabakhsh; Maryam Jamshidi (University of Social Welfare and Rehabilitation Sciences, 2008)
Objective: Among the traditional and modern drugs, appearance and spreading of ecstasy drugs is a new phenomenon that has affected different nations, among them Iranian youth. While, it seems that unawareness in society of these industrial drugs, has a great influence in spreading its use. This research was conducted to evaluate students' knowledge about the effects of ecstasy drugs.  Materials & Methods: This study is a descriptive and cross-sectional research. 154 high school students, by simple random sampling, in district 9 of Tehran were selected and their awareness about research object were evaluated by researcher made questionnaire. The face validity of questionnaire was confirmed by specialists consideiation and its rehabilitee was confirmed by Cronbach's alpha coefficient (r = 0.85). Data were analyzed by Correlation coefficient and Mann-Whitney U.  Results: 14.7 percent of responses were incorrect, and 38 percent were don't know. Students' awareness of accidents and bad effects of ecstasy drugs is in a low level. There was no significant difference between boys and girls' knowledge about the effects of ecstacy (P= 0.573). Also, there was no significant relation between student sexuality and their awareness about Ecstasy side effects (P=0.572). Conclusion: Students' knowledge about the Effects of ecstasy drugs is in a low level (47.3 percent).